Development of a Balaghah Module with Interactive Assignments: Enhancing Literary Appreciation in Pesantren Environments - Nurul Musyafa'ah; Endang Munawar; Fatya Nia Rahmawati; Devi Eka Diantika; Fachrul Rozi (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study aims to enhance literary appreciation among Pondok Pesantren Adnan Al-Charis students through a Balaghah learning module. It evaluates the module's effectiveness in improving students' understanding and interest in literary materials, employing quantitative and qualitative methodologies, including surveys, interviews, and tests. Findings reveal that 85% of students report increased interest in learning Balaghah after using the module, with average test scores improving from 62 to 82, indicating significant gains in comprehension. Validation by education experts confirms the module's appropriate structure and methodology, while classroom observations show heightened student participation in discussions. Although there are critiques regarding disparities in achievement and technology access, this research underscores the module's potential as an innovative teaching model for Balaghah. Ultimately, this study contributes to developing effective teaching materials and fosters an interactive learning environment, aiming to cultivate students who appreciate the beauty of Arabic literature.